Trade-offs and synergies associated with maize leaf stripping within crop-livestock systems in northern Ghana - Komarek, Adam M.; Rahman, N.A.; Bandyopadhyay, A.; Kizito, Fred; Koo, Jawoo; Addah, W. (Elsevier, 2021)
CONTEXT The accessibility and availability of forages is a common concern in crop-livestock systems in West Africa; however, options to increase forage production may entail trade-offs within the farm system that can be challenging to quantify explicitly.